PENGARUH DUKUNGAN PEER GROUP TERHADAP SELF-CARE MANAGEMENT PADA PENDERITA HIPERTENSI - Khoiriyah, Siti; Fahrurozi, M.; Mustajab, Abdullah Azam (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2024)
Hypertension is a non-communicable disease known as the silent killer and is the leading cause of death worldwide. The aim is to determine the effect of a specific type of peer group support, such as educational sessions or emotional support, on self-care management in hypertension sufferers. The research method uses a pre-experiment with one group pretest-posttest design. The sample uses purposive sampling, where samples that meet the inclusion criteria will be measured for their level of self-care management before and after the intervention. The research data were tested for normality, and then a paired sample t-test was conducted to determine the difference in the level of self-care management before and after the peer group support intervention was given. The results of the study explained that before the peer group support intervention, the level of self-care management of respondents was sufficient 18 (60%), lacking 6 (20%) and good 6 (20%) with the lowest value of self-care management of respondents 58 and the highest value of respondents 153. After the peer group support intervention, respondents' self-care management level increased to good 16 (53.3%) and sufficient 14 (46.7%), with the lowest value of self-care management of respondents 83 and the highest value of respondents 156. Peer group support, in the form of a specific type of support, affects the self-care management of hypertension sufferers. Keywords: blood pressure, hypertension, peer group support, self-care management